Glycemic index of selected watermelon (Citrullus lanatus) - Sarmin, Sabeetha; Mohd Yusof, Barakatun Nisak; Ismail, Amin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
The glycemic index (GI) was conducted on 14 healthy subjects who have consumed 25 g of available carbohydrate portions of glucose (standard food) and four test foods (red-fleshed seedless watermelon, red-fleshed seeded watermelon and yellow-fleshed watermelon, as well as a glass of red-fleshed seedless watermelon juice) in random order after an overnight fast. Red-fleshed seedless watermelon was usually processed as juice than red-fleshed seeded and yellow-fleshed watermelon. Blood glucose was measured at 0, 15, 30, 45, 60, 90 and 120 mins after intake of the foods. Incremental areas under the curve were calculated, whereas the glycemic index was determined by expressing the area under the curve after the test foods, as a percentage of the mean area under the curve after consuming standard food, was carried out. The results showed that the area under the curve for a portion of red-fleshed seedless was 98.17±6.39, red-fleshed seeded (94.10±7.45), yellow-fleshed (92.95±8.73), and a juice of redfleshed seedless (98.89±6.38) did not have any significant difference (p < 0.05). The GI of a portion fruit and the juice of red-fleshed seedless watermelon were 51, while red-fleshed seeded watermelon was 48 and yellow-fleshed watermelon was 47. The study showed red-fleshed watermelon and yellow-fleshed watermelon could be classified as low GI food (GI value below 51) with strong influenced by the fructose content and no significant difference from GI value among red and yellow watermelons. This research will help the experts to explore more based of GI value and also be used as a database reference.